A morphological and histological investigation of the regeneration in Myxicola infundibulum (Montagu, 1808) (Sabellida, Annelida). (13th March 2017) - Prentiss, Nancy K.; Tyler, Mary S.; Dean, David
Abstract : Anterior regeneration of the annelid polychaete, Myxicola infundibulum (Montagu, 1808) is described from histological and SEM perspectives. This article provides additional evidence that anterior and posterior regeneration of isolated worm pieces does occur in this species, but that regenerative ability is restricted to abdominal pieces obtained from small individuals (less than 5 mm in thorax diameter and 10–20 mm in length). New cartilage tissue forms within the regenerating crown, but thoracic regeneration is limited to three segments. Anterior and posterior regeneration occurred within isolated pieces excised from the abdomen, resulting in the formation of 13 clones, with up to five individuals per clone.